Effect of oatmeal on texture, water mobility, and starch retrogradation properties of Chinese steamed bread. Issue 2 (28th January 2019) - Liu, Yu; Wang, Xiaolong; Ren, Tian; Ma, Zhen; Liu, Liu; Li, Xiaoping; Guo, Qingbin; Hu, Xinzhong
Abstract: Background and objectives: The study aimed to characterize the effect of oatmeal on the texture, water mobility, and starch retrogradation properties in Chinese steamed bread (CSB). Oatmeal substitution was set as 0%, 10%, and 30%. Findings: With the addition of oatmeal in CSB, higher hardness and chewiness and lower resilience were observed compared to the control ( p  < 0.05); CSB with addition of oatmeal exhibited a lower rate of increase in hardness than that of the control. Oatmeal increased the water holding capacity of CSB and restricted water migration, which resulted in a lower content of immobilized water (S22, 76.72%–77.03%) and higher content of free water (S23, 1.01%–1.07%) in NMR. Results from differential scanning calorimetry, X‐ray diffraction, and fourier transform infrared suggested that with the increase in oatmeal, the enthalpy and the relative crystallinity of CSB reduced. The addition of oatmeal retarded a stable and ordered state of starch structure formed in CSB during storage at room temperature. Oatmeal decreased the starch retrogradation rate constant k and CSB with 30% of addition of oatmeal had the lowest k value (10.1), indicating its inhibitory effect on the formation of starch crystals. Conclusions: Our findings revealed that oatmeal could increase the free water of CSB and restrict water migration, thus retarding starch retrogradation in CSB. Significance and novelty: Oatmeal could effectively inhabit water migration and starch retrogradation of CSB, consequently inhibiting the staling, and there could be a potential utility of oatmeal in the development of flour‐based food products.